2008
DOI: 10.1108/02686900810899545
|View full text |Cite
|
Sign up to set email alerts
|

The impact of harmonisation by the International Federation of Accountants

Abstract: PurposeThe purpose of this paper is to examine the impact of the new, revised International Standard on Auditing (Revised ISA700) in terms of the wording characteristics of Tunisian auditors' reports.Design/methodology/approachMeasurement of the compliance of auditors' reports issued by Tunisian auditors with the new revised International Standard on Auditing (Revised ISA700).FindingsIt was found that the audit reports examined are not fully compliant with all the elements enumerated by the new standard issued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Auditing standards should consider the linguistic rules to improve the readability of auditing reports. Empirically, several determinants may explain the variability of readability of standardized illustration of audit reports (Fakhfakh, 2013). Among the explanatory variables of this phenomenon, we can consider: the impact of the translation of international standards on auditing, the impact of the modification of the auditor's opinion and the impact of the reform of standards on auditors' reports.…”
Section: Implication Of Results and Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Auditing standards should consider the linguistic rules to improve the readability of auditing reports. Empirically, several determinants may explain the variability of readability of standardized illustration of audit reports (Fakhfakh, 2013). Among the explanatory variables of this phenomenon, we can consider: the impact of the translation of international standards on auditing, the impact of the modification of the auditor's opinion and the impact of the reform of standards on auditors' reports.…”
Section: Implication Of Results and Final Remarksmentioning
confidence: 99%
“…Audit professionals produce texts that summarize the work of control and audit results. Several empirical studies have shown that the reports of the independent financial auditors are not understood by many readers of the financial statements (Barnett & Leoffler, 1979;Hay, 1998 andFakhfakh, 2013). In addition, accounting research has discussed the problem of expectation gap which results from the misunderstanding of the significance and the direction of the audit opinion formulations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Profitability of a company reflects the level of effectiveness achieved by a company's operations. Rationale that the level of profit used as one way to assess the success of the company's effectiveness is of course related to the final result of the company's policies and decisions that have been implemented by the company in the current period (Fakhfakh: 2013a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study focussed on the readability of standardized reports by the IFAC was conducted by Fakhfakh (2013). The purpose of this research is to examine the readability of reports which have been standardized by three ISAs (ISA 700, ISA 705 and ISA 706).…”
Section: Ara 241mentioning
confidence: 99%